The Effects of Principals’ Digital Leadership on Teachers’ Digital Teaching during the Covid-19 Pandemic in Malaysia - Hamzah, N. Hafiza; Nasir, M. Khalid M.; Wahab, Jamalullail Abdul (Journal of Education and e-Learning Research, 2021)
Education involving digital technology is the latest transformation of the education system, especially during the occurrence of the COVID-19 pandemic. The Malaysian Ministry of Education (MOE) has taken the initiative to spearhead efforts to develop the skills and potential of students in the use of digital technology. The main purpose of this study was to identify the level of digital leadership displayed by principals, the level of teachers' digital teaching practices and the elements of principals' digital leadership that predict the level of teachers' digital teaching. About 400 secondary school teachers in Hulu Langat District, Selangor were involved in this study. The findings of this study show that the level of digital leadership displayed by principals and teachers’ digital teaching practice are both at a high level. However, the positive correlation between the two is moderate. Multiple regression found that only digital citizenship is a strong predictor of teachers' digital teaching. The findings show that the ability to plan and organize digital leadership programs is important and can help improve students' academic performance, despite the COVID-19 pandemic crisis.